GARFIELD-AF: risk profiles, treatment patterns and 2-year outcomes in patients with atrial fibrillation in Germany, Austria and Switzerland (DACH) compared to 32 countries in other regions worldwide - Haas, Sylvia; Camm, John A.; Harald, Darius; Steffel, Jan; Virdone, Saverio; Pieper, Karen; Brodmann, Marianne; Schellong, Sebastian; Misselwitz, Frank; Kayani, Gloria; Kakkar, Ajay K.; Hacke, Werner (Clinical research in cardiology, 2023)
BACKGROUND: The Global Anticoagulant Registry in the FIELD-Atrial Fibrillation (GARFIELD-AF) is a worldwide non-interventional study of stroke prevention in patients with non-valvular AF. METHODS AND RESULTS: 52,080 patients with newly diagnosed AF were prospectively enrolled from 2010 to 2016. 4121 (7.9%) of these patients were recruited in DACH [Germany (n = 3567), Austria (n = 465) and Switzerland (n = 89) combined], and 47,959 patients were from 32 countries in other regions worldwide (ORW). Hypertension was most prevalent in DACH and ORW (85.3% and 75.6%, respectively). Diabetes, hypercholesterolaemia, carotid occlusive disease and vascular disease were more prevalent in DACH patients vs ORW (27.6%, 49.4%, 5.8% and 29.0% vs 21.7%, 40.9%, 2.8% and 24.5%). The use of non-vitamin K antagonist oral anticoagulants (NOACs) increased more in DACH over time. Management of vitamin K antagonists was suboptimal in DACH and ORW (time in therapeutic range of INR ≥ 65% in 44.6% and 44.4% of patients or ≥ 70% in 36.9% and 36.0% of patients, respectively). Adjusted rates of cardiovascular mortality and MI/ACS were higher in DACH while non-haemorrhagic stroke/systemic embolism was lower after 2-year follow-up. CONCLUSIONS: Similarities and dissimilarities in AF management and clinical outcomes are seen in DACH and ORW. The increased use of NOAC was associated with a mismatch of risk-adapted anticoagulation (over-and-undertreatment) in DACH. Suboptimal control of INR requires educational activities in both regional groups. Higher rates of cardiovascular death in DACH may reflect the higher risk profile of these patients and lower rates of non-haemorrhagic stroke could be associated with increased NOAC use.